Association of TGF-β1, IL-4, and IL-10 Polymorphisms With Chronic Kidney Disease Susceptibility: A Meta-Analysis - Mai, Meifang; Jiang, Yinlian; Wu, Xiaoman; Liu, Gengrong; Zhu, Yaoli; Zhu, Weiping (Frontiers in Genetics, 2020)
Background: Anti-inflammatory cytokine polymorphisms in the transforming growth factor-β1 (TGF-β1), interleukin-4 (IL-4) and IL-10 genes have been implicated as risk factors for chronic kidney disease (CKD), but the results from published studies are inconsistent. Our meta-analysis reviews and summarizes the cumulative evidence for these associations. Methods: A systematic literature search of 5 databases was performed up to October 2019. Two authors independently extracted data and evaluated the quality of included studies. Pooled odds ratios (ORs) and 95% confidence intervals (CIs) were generated from random-effects or fixed-effects models using Stata 12.0. Results: Nineteen case-control studies from 11 countries satisfied our inclusion criteria and were included in the meta-analysis. Overall, the pooled analysis showed that TGF-β1 rs1800469 was associated with decreased susceptibility to CKD (CC + TC vs TT, OR=0.33, 95% CI: 0.15-0.76, P=0.009; CC vs TT, OR=0.33, 95% CI: 0.15-0.73, P=0.006), whereas TGF-β1 rs1800471 was associated with increased CKD susceptibility (CC vs CG + GG, OR=1.68, 95% CI: 1.02-2.77, P=0.041; ). In stratified analyses based on ethnicity, TGF-β1 rs1800469 was associated with CKD susceptibility in Asians and Caucasians, and there was an association of TGF-β1 rs1800470 and IL-4 rs8179190 with CKD in Asians. Stratified analyses also associated TGF-β1 rs1800471 with CKD susceptibility in Caucasians. Neither overall meta-analyses nor stratified analyses identified an association of the IL-10 rs1800869 and rs1800871 polymorphisms with susceptibility to CKD. Conclusions: Available data suggest that common polymorphisms in the TGF-β1 and IL-4 genes including rs1800469, rs1800470, rs1800471 and rs8179190 may be important genetic contributors to CKD susceptibility.